2018
DOI: 10.1007/s12035-018-0876-4
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Gene Expression in Treatment-Resistant Schizophrenia

Abstract: Schizophrenia (SCZ) is a mental disorder arising from a complex interaction of genetic and environmental factors. It has been suggested that treatment-resistant schizophrenia (TRS) is a distinct, more severe, and homogenous subgroup of schizophrenia that could present specific biological markers. Our aim was to characterize expression of target genes in blood of TRS patients compared with non-TRS (NTRS) patients and healthy controls (HC). TRS has been defined using failure to respond to two previous antipsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 61 publications
5
25
0
2
Order By: Relevance
“…In our study, both male and female patients with TRS had significantly higher PANSS total, positive, negative, and general psychopathology scores, as well as higher chlorpromazine equivalent doses in comparison to male and female patients in non-TRS group. This is in agreement with previous studies reporting that patients with TRS had more severe symptomatology as measured by PANSS ( Moretti et al, 2018 ) and received higher total antipsychotic dose presented as chlorpromazine equivalents, compared to patients with non-TRS ( Hotta et al, 2011 ; de Bartolomeis et al, 2018 ; Moretti et al, 2018 ). In the present study, the concentration of antipsychotics in plasma was not measured.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, both male and female patients with TRS had significantly higher PANSS total, positive, negative, and general psychopathology scores, as well as higher chlorpromazine equivalent doses in comparison to male and female patients in non-TRS group. This is in agreement with previous studies reporting that patients with TRS had more severe symptomatology as measured by PANSS ( Moretti et al, 2018 ) and received higher total antipsychotic dose presented as chlorpromazine equivalents, compared to patients with non-TRS ( Hotta et al, 2011 ; de Bartolomeis et al, 2018 ; Moretti et al, 2018 ). In the present study, the concentration of antipsychotics in plasma was not measured.…”
Section: Discussionsupporting
confidence: 93%
“…et al, 2011 ). Moreover, there were no differences between patients with and without TRS in the whole-blood gene expression of 13 genes, including COMT gene ( Moretti et al, 2018 ).…”
Section: Introductionmentioning
confidence: 93%
“…By contrast, increased ReHo was found in the left postcentral gyrus in TRS compared with NTRS, and decreased ReHo was observed in the left postcentral gyrus in NTRS relative to HCs. In line with our findings, Gong et al ( 30 ) revealed that Disrupted in Schizophrenia Gene 1 (DISC1) was related to the postcentral gyrus, suggesting that TRS may have distinct heredity as a special subgroup ( 4 ). Moreover, by using positron emission tomography, Monika et al ( 25 ) discovered that the bilateral postcentral gyrus in patients with auditory hallucination showed increased metabolism, indicating that this region is a cue for explaining the increased ReHo values and symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Treatment-resistant schizophrenia (TRS) is characterized by the lack of response to two kinds of antipsychotics at doses ≥ 400 mg/day equivalents of chlorpromazine for a minimum period of 4–6 weeks, and with continuing moderate to severe psychopathology (especially positive symptoms) ( 3 ). TRS has been regarded as a severe and homogenous subgroup of schizophrenia that presents specific biological markers ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…62 A study comparing gene expression among patients with TRS, patients with treatment-responsive schizophrenia, and healthy controls found no difference between the groups with schizophrenia in the expression of 13 candidate genes, including COMT. 63 Although there are inconsistencies and variability among the results of some of these highlighted studies, several candidates for the biological mechanisms or subtypes of TRS require further research. Additional studies are needed to further characterize these candidate biological mechanisms and to identify new treatment targets.…”
Section: Genetic Variants That May Contribute To Schizophrenia or Trsmentioning
confidence: 99%